Tolerability for older, persistence for younger: a real-world evidence on sacubitril/valsartan in an Asian heart failure cohort across age - Po-Kai Chan; Po-Kai Chan; Chu-Yu Hsu; Chao-Chin Lee; Chao-Chin Lee; Fan-Han Yu; Fa-Po Chung; Fa-Po Chung; Chia-Te Liao; Chia-Te Liao; Jin-Long Huang; Jin-Long Huang; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundSacubitril/Valsartan (S/V) benefits patients with heart failure with reduced ejection fraction (HFrEF), but its tolerability and clinical outcomes across age groups, especially the elderly, remain unclear. This real-world study evaluates these factors in an Asian cohort.MethodsThis retrospective cohort study analyzed data from the Treatment with Angiotensin Receptor Neprilysin Inhibitor for Taiwan Heart Failure Patients (TAROT-HF) registry (2017–2018). Patients were stratified into three age groups: <65, 65–74, and ≥75 years. Tolerability was defined as achieving at least 50% of the target S/V dosage (200 mg/day). Baseline characteristics, treatment doses, and clinical outcomes—including the composite of first unplanned heart failure hospitalization (HFH) or cardiovascular (CV) death, all-cause mortality, CV death, and HFH—were assessed over 5 years.ResultsAmong 1,987 patients, older adults had more comorbidities and received lower S/V doses. Achieving tolerability significantly reduced composite outcome risk in patients <65 (HR = 0.40, 95% CI: 0.27–0.59, p < 0.001), all-cause mortality (HR = 0.30, p < 0.001), CV death (HR = 0.41, 95% CI: 0.21–0.80, p = 0.009), and HFH (HR = 0.41, 95% CI: 0.27–0.62, p < 0.001). Those aged 65–74 had similar benefits except for CV death. In patients ≥75, reaching tolerability improved composite outcome (HR = 0.60, 95% CI: 0.39–0.91, p = 0.017) and HFH (HR = 0.60, 95% CI: 0.38–0.95, p = 0.029). Partial dosing still provided protection in younger patients.ConclusionS/V improves HFrEF clinical outcomes across age groups in an Asian population, especially when achieving tolerability, defined as reaching ≥50% of the target dose. While this association was less pronounced in older patients, our result suggested that individualized dosing strategies should prioritize persistence in younger patients while accommodating tolerability in older populations.